2017
DOI: 10.1097/iio.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging in Dry Eye

Abstract: Dry eye affects millions of people worldwide and causes eye well recognized risk factors for dry eye. Anatomical and inflammation-induced age-related changes affect all components of the lacrimal gland functional unit, inclusive of lacrimal gland, conjunctiva, meibomian gland and compromise ocular surface health. There is increased evidence that inflammation plays a role in dry eye. This review will summarize the current knowledge about aging and dry eye, inclusive of lessons learned from animal models and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
5
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 181 publications
3
87
5
8
Order By: Relevance
“…Given that tear and protein secretion are energy-requiring active procedures, the LGs appear to be highly susceptible to pathological aging. Emerging evidence suggests that the LGs undergo inflammation, atrophy, fibrosis, or ductal cell proliferation with aging in humans, as well as rodents [6,[9][10][11]. Aging impairs the LGs by altering multiple mechanisms, such as neuroendocrine, immunological, apoptotic, protein secretion, and oxidative stress pathways [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that tear and protein secretion are energy-requiring active procedures, the LGs appear to be highly susceptible to pathological aging. Emerging evidence suggests that the LGs undergo inflammation, atrophy, fibrosis, or ductal cell proliferation with aging in humans, as well as rodents [6,[9][10][11]. Aging impairs the LGs by altering multiple mechanisms, such as neuroendocrine, immunological, apoptotic, protein secretion, and oxidative stress pathways [11].…”
Section: Discussionmentioning
confidence: 99%
“…Data are presented as means ± standard error. 6, and 3 for 8W-, 1Y-, and 2Y-old mice, respectively). Ns, not significant; *p < 0.05 and ****p < 0.0001.…”
Section: Ded Was Established In Aged C57bl/6 Male Micementioning
confidence: 96%
See 1 more Smart Citation
“…[47][48][49] While there are large scale studies that failed to show a significant difference in success rates between presbyopic and non-presbyopic contact lens wearers, 16 setting realistic expectations with "real world" testing of multifocal contact lenses and using the latest multifocal designs and materials may prove to be uniquely successful when fitting presbyopic patients. Unfortunately, conditions such as dry eye are more common in this group of patients, 50 which is an additional hurdle that may promote contact lens dropout in presbyopic patients. 51 Again, as described above, early treatment may promote additional years of comfortable contact lens use.…”
Section: Combatting Contact Lens Dropoutmentioning
confidence: 99%
“…However, it is suggested that DES is related to biochemical, molecular and immune system disturbances. 16 Dry eyes are an unfortunate side effect of radiotherapy. Radiotheraphy causes damage to the cells that leads to necrosis and apoptosis, resulting in the release of inflammatory mediators that are responsible for dry eye syndrome.…”
Section: Dry Eyes In Common Clinical Conditionsmentioning
confidence: 99%